Beyond existence [videorecording (DVD)] - Farah, Steven; Clay, Amelia; MacKay, Gary; Vermignon, Vincent, 1983-; Abedi, Bamshad; McKenna, Jon; Turner, Pauline (Indican Pictures, 2023)
CIA Agent Ellen Jones is sent on a mission to neutralize a professor who's been illicitly trading government information to foreign powers. However, the Professor reveals a source of intelligence so powerful that Ellen has no choice but to spare the Professor's life. The unlikely couple set across the barren landscapes of Europe on a new mission to save humankind as they are hunted by a time-traveling bounty hunter known as The Guardian.